A Call to Action: Gain a Seat at Decision Tables. Issue 1 (January 2017) - Johnson, Sazara R.
Abstract : No matter how much HPT practitioners improve human performance, we are not granted enough invitations to serve as tactical and strategic decision makers. Many "earning" decision makers such as financial experts regard HPT professionals as no more than operational‐level learning professionals. Therefore, HPT practitioners cannot rely on current decision makers to initiate a call for increased respect for the HPT industry. However, there is a contingent of HPT practitioners known as business‐entity performance technologists (BEP Techs) who serve as HPT activists by obtaining influential roles in decision processes. Their goals are to influence decision makers, become decision makers, support decision makers, and challenge decision makers from other industries to respect HPT practitioners as more than just learning professionals. To do this, they focus more on the improvement of business‐entity performance than on human performance. They seek to obtain respect for the HPT industry as both learning and earning professionals.